The structure and dynamics of R and D collaborations in Europe and the USA (A longitudinal and comparative perspective) - Sidonia von Proff; Rafael Lata; Thomas Brenner (Philipps-University Marburg, Department of Geography, 2014)
Today it is generally accepted that innovation, knowledge creation, and the diffusion of new knowledge are crucial factors for economic growth at the regional, national, as well as supra-national level, and that successful innovation is increasingly based on interactions and collaborative research activities between research actors. This study focuses on diverse dimensions of distance shaping R and D collaborations in Europe and the US during the time period 1999 to 2009. We take a comparative perspective by analyzing two different R and D collaboration networks (patents and publications) and two different economic areas, namely Europe and the US, in order to examine differences in collaboration activities. In particular, we investigate how the collaboration intensity between regions has been influenced by spatial, technological, and cultural distance and whether these distances have lost importance over time in the distinct networks. The study adopts a panel spatial interaction modeling perspective. In doing so, we explicitly take account of spatial autocorrelation issues of flows by means of Eigenvector spatial filtering techniques. European coverage is achieved by using 1260 NUTS-3 regions of the 25 pre-2007 EU member-states, as well as Norway and Switzerland. The US coverage is attained by using 955 core based statistical areas (CBSAs). The results reveal how collaborative knowledge creation and the spatial range of knowledge diffusion differs between Europe and the US, and provide direct evidence on the differences in cooperation patterns between different types of collaborative R and D from a longitudinal and comparative perspective
Keywords: C23; O38; L14; R15; 330; R and D Networks; Patents; Publications; Spatial Interaction Modeling; Eigenvector Spatial Filtering; distance